Reguladores vegetais na produção de biomassa e teor de óleos essenciais em Cymbopogon citratus (DC.) Stapf, em diferentes épocas do ano - Figueiredo, R. O. [UNESP]; Delachiave, Maria Elena Aparecida [UNESP]; Ming, Lin Chau [UNESP] (My University, 2006)
The purpose of the present research was to evaluate the effect of plant growth regulators in biomass production and essential oil yield content in lemongrass (Cymbopogon citratus (DC.) Stapf), in different seasons. The experiment was conducted on São Manuel Experimental Farm, Faculdade de Ciências Agronômicas, UNESP - Botucatu. Which plants were randomly assigned into blocks to treatments with three repetitions. The treatments consisted of GA3 (50 and 100 mg L-1); Ethrel (100 and 200 mg L-1); CCC (500 and 1000 mg L-1); Alar 85 (1000 and 2000 mg L-1); Accel (20 and 40 mg 0L-1) and control. Four applications of plant growth regulators were realized every three months. After 40 days of each foliar spray, the plants were cut to determine the fresh weight and essential oil yield. The application of plant growth regulators did not increase the biomass production, showing difference among collect periods when the major production was detected at the fourth collect (summer). The greatest essential oil yield was found at the second collect (winter). In the present study, the used concentrations of plant growth regulators did not increase biomass neither essential oil yield.
Growth regulators in biomass production and essential oil in Cymbopogon citratus (DC.) Stapf, in different seasons
Keywords: Biomass; Cymbopogon citratus; Growth regulators; Oils volatile; essential oil; phytohormone; biomass production; plant yield component; seasonal variation